2014
DOI: 10.1186/1471-2407-14-54
|View full text |Cite
|
Sign up to set email alerts
|

A panel of genes methylated with high frequency in colorectal cancer

Abstract: BackgroundThe development of colorectal cancer (CRC) is accompanied by extensive epigenetic changes, including frequent regional hypermethylation particularly of gene promoter regions. Specific genes, including SEPT9, VIM1 and TMEFF2 become methylated in a high fraction of cancers and diagnostic assays for detection of cancer-derived methylated DNA sequences in blood and/or fecal samples are being developed. There is considerable potential for the development of new DNA methylation biomarkers or panels to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 40 publications
7
117
0
2
Order By: Relevance
“…Similarly to the finding of ATM, CHEK2 also participates in the DNA damage response progress, and further related to the tumor metastasis [20]. An existing study found the DLX5 showed DNA methylation in >50% CRC tissue, which is in line with our observation [21]. DLX5 also has been found important as a cancer-hypermethylated gene with demonstrated tumor-suppressor functions.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly to the finding of ATM, CHEK2 also participates in the DNA damage response progress, and further related to the tumor metastasis [20]. An existing study found the DLX5 showed DNA methylation in >50% CRC tissue, which is in line with our observation [21]. DLX5 also has been found important as a cancer-hypermethylated gene with demonstrated tumor-suppressor functions.…”
Section: Discussionsupporting
confidence: 76%
“…However, the methylation analysis showed a relatively high incidence of FOXF1 methylation among lung cancer patients and lung tumoral cell lines. Mitchell SM et al [26] and PK Lo et al [27] also found an important percentage of FOXF1 methylation in colorectal cancer and breast cancer. Our results, however, showed that FOXF1 expression could by silenced by promoter methylation also in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…lung, bladder, and stomach (38). For the other genes, BCAT1 (branched chain amino-acid transaminase 1) is a cytosolic enzyme that promotes cell proliferation though amino acid catabolism (39) and high frequency of methylation on BCAT1 promoter in colorectal cancer has been reported (40). ZNF177 is a zinc finger transcription factor that has been reported to be methylation-silenced in gastric cancer cell lines (41).…”
Section: Discussionmentioning
confidence: 99%